Legal Aid and Human Rights : A Reflection - Alex Chandra (Jurnal Meta-Yuridis, 2023)
Humanity and Human Rights is a concern of mankind throughout the world. Therefore, the consequences if there is a violation of human rights anywhere in the world will be a concern for humans everywhere in this world. The difficulty that is faced with this "Human Rights" is that Human Rights have a different meaning for everyone. Historians, jurists, philosophers and theologians can differ in stating something that has significant implications for human rights, and all these differing opinions must be examined. Some parties will seek definitions of “Rights” and “Obligations” and of course “Freedoms”. Other parties will argue about whether humans have inherent rights that are inherent and rooted in every human being.